Numerical and experimental investigation on the effect of tire on the 13° impact test of automotive wheel. (July 2019) - Wan, Xiaofei; Liu, Xiandong; Shan, Yingchun; Jiang, Er; Yuan, Haiwen
Highlights: The finite element model of tire considering the structural and material nonlinearity is established in terms of the real tire. The simulations of 13° impact test of automotive wheel are performed, and the results are verified by experimental result. The effects of tire on wheel during the impact test are discussed, and a conclusion of the tire has dual effects on wheel performance is drawn. Abstract: The effect of tire on the wheel should be considered in detail in the process of simulating 13° impact test of the automotive wheel. However, due to the complexity and nonlinearity of the tire, the tire is usually simplified or neglected in the current simulation of wheel impact test, and these often lead to insufficient simulation accuracy. In this paper, a numerical simulation approach is proposed to evaluate the impact performance of wheel, in which the finite element model of tire is established in terms of the real tire. The physical wheel 13° impact tests are also performed, and the comparison between the simulation and experiment indicate that the proposed simulation method provides an efficient tool for predicting the impact performance of the wheel in wheel 13° impact test. Furthermore, the effects of tire on wheel are discussed by comparing the simulation and experiment results, and the results show the tire has a dual effect on wheel performance during the wheel 13° impact test.